Composition, diversity and functional potential of bacterial community in four stony coral species from the South China Sea - Li, Zimu; Liao, Xinyu; Mo, Li; Liao, Qi; Lin, Kaijun; Bao, Xinyi; Sun, Jijia; Zhang, Xiaoyong (Frontiers in Microbiology, 2026)
Recent investigations of coral symbiotic microorganisms have largely centered on their ecological functions, while systematic analyses of the community composition, diversity, and functional potential of bacteria associated with different coral species remain limited. This study presents the first systematic analysis of the distinct community structures and highly conserved core functions of symbiotic bacteria in four species of stony corals Favites abdita (Fa), Favia speciosa (Fs), Montipora digitata (Md), and Porites solida (Ps) from the South China Sea by high-throughput sequencing. The results identified 23 phyla and 250 genera of bacterial taxa, revealing considerable taxonomic richness in these coral-associated bacterial communities. Significant differences (p < 0.05) in bacterial community composition were observed among four coral species. Proteobacteria was the absolutely dominant phylum in Fa, Fs, and Ps, whereas Md was dominated by the phylum Firmicutes. At the genus level, the core microbial communities of the four coral species were similar in composition but exhibited marked differences in abundance. Md showed the highest species richness and diversity, and Fs the lowest. Among them, the Fa, Fs, and Ps groups were dominated by Ruegeria, while the Md group was characterized by a high abundance of Paramaledivibacter, which was significantly more abundant than in other groups. Functional prediction indicated that the relative abundances of core functional categories, such as amino acid transport and metabolism and energy production and conversion, were highly consistent across the four coral species, reflecting functional conservation within these communities. These findings enrich the basic data on the diversity and function of Coral symbiotic microorganisms in the South China Sea, revealing the connection between coral community variability and the conservation of core functions.